Análisis empírico de la producción de Fréjol Arbustivo en la Parroquia Multitud, Cantón Alausí, Provincia de Chimborazo, período 2021. - Chavez Gavilanez, Julio Abel (2022)
It is intended to estimate the participation of the productive factors in the bush bean production process by the farmers of the Multitud parish, Alausí canton, Chimborazo province, and the type of scale returns that it presents for the year 2021. 62 questionnaires were applied to bush bean producers. With the information collected, a Cobb Douglas-type production function was estimated, in which the type of returns to scale and the participation of production factors are evaluated: wages, seeds, fungicides, insecticides, herbicides, in the amount harvested. The results show that the participation of the seed factors, number of wages and expenditure on herbicides in the amount harvested is 0.3053; 0.4072 and 0.2711 respectively. In other words, for each time in which one of the factors increases by 1%, production will vary positively by 0.31%; 0.41%; 0.27% under the condition of ceteris paribus. Spending on insecticides and fungicides were not significant. In the same way, production shows scale diminishing returns. It is concluded that production is intensive in the quantity of seeds and presents scale decreasing returns, that is, when the use of factors increases simultaneously, production will grow, but in less proportion to the increase of factors.